Design of Ultrasonic Excitation Circuit based on Half-Bridge Circuit - Deng, Yong; Liu, Jiewen (Scientific Journal of Technology, 2025)
The excitation circuit of ultrasonic probe is the key and core part of the ultrasonic testing system. It ensures that the ultrasonic probe can work normally. It is a challenging design in ultrasonic testing technology, and its design quality affects the resolution and accuracy of the testing system. The piezoelectric crystal in the ultrasonic probe emits ultrasonic wave by piezoelectric effect to realize the conversion of voltage signal and stress signal. The waveform parameters of ultrasonic wave are positively correlated with the waveform parameters of voltage excitation signal. The same echo signal acts on the piezoelectric crystal to generate voltage signal to realize ultrasonic wave detection. In ultrasonic testing, due to the difference between the acoustic impedance of the tested workpiece and the coupling agent, the loss is large in the transmission process. The design goal of this design: Based on half-bridge circuit and bootstrap circuit, a pulse voltage transmitting circuit with low power consumption and adjustable pulse width and frequency parameters is developed. High voltage pulse, square wave pulse and sharp pulse excitation are often used in ultrasonic probe. This design focuses on the excitation of high voltage pulse.